Sistema de humanización urbano (2016)
"The project seeks to focus on the space located below the metro line and transform in an environment with urban potential for the city, avoiding the possibility of it becoming a residual space in Bogota. To achieve this, the main strategy is based on giving the immediate street of the metro its character of public place, through the activities that in this event, encourage social relations and privilege the pedestrian but the car. The shared street is the essence that is implanted in the Primera de mayo Avenue, from the street 40 to the street 37d south. In the area that is located about 400 meters from the Avenida de Mayo, where vehicles circulate on the actual surface, which responds to the subway, priority is given to the pedestrian and to the different activities that enhance and humanize the new profile of the Street".-- Tomado del Formato de Documento de Grado.